The construction of the State in a border region: Puno 1825-1836 - Monrroy Anco, Gustavo Alfonso (2021)
This paper studies the process of state development in Puno through the prefects. This process was marked by two parallel objectives: integration into the Peruvian state and differentiation with Bolivia. Puno was considered a strategic region for the initial state because of its mining production, revenue collection through personal contributions, and status as a border zone. The Prefects, despite the instability and economic precariousness, tried to comply with demanded priorities by the state in the area, resorting to negotiation, suggestion, or opposition. The prefects were more successful in revenue collection and military control, while mining promotion and contraband control had little results.